Integration Of The Living Values Education Program (LVEP) In The Merdeka Curriculum - Mahilda Dea Komalasari; An-Nisa Apriani (Universitas PGRI Yogyakarta, 2023)
This study is important for examine the integration of the Life Values Education Program (LVEP) into the Merdeka Curriculum. This research is important because character is one of the crucial aspects that affect the progress of the nation. To create a nation with character, strategic steps are needed. This research is a descriptive qualitative research with a literature review. The results of this study are that the merdeka curriculum is an idea that frees teachers and students in determining the learning system. The merdeka curriculum aims to create fun learning for teachers and students because so far education in Indonesia has emphasized knowledge rather than affective or skill aspects. The merdeka curriculum also emphasizes aspects of character development that are in accordance with the values of the Indonesian nation which are summarized in the Pancasila student profile. LVEP has been integrated into the Merdeka Curriculum but there are several obstacles faced by teachers in implementing it. Obstacles related to understanding range from not understanding the essence of the merdeka curriculum. As well as difficulties in creating teaching modules that integrate LVEP. Finally, at the evaluation stage, teachers experience difficulties in making assessments related to LVEP integration.